Educational Management of PAI Learning Integrating Factual, Conceptual, Procedural, and Metacognitive Knowledge Dimensions - Mateka, Nikmayanti S.; Yahiji, Kasim (Al-Qalam Institue, 2026)
This study aims to examine the dimensions of knowledge—factual, conceptual, procedural, and metacognitive—in Islamic Religious Education (PAI) learning as mandated by Regulation of the Minister of Education and Culture Number 54 of 2013. Employing a library research method, this study analyzes various academic sources, including books, journals, official curriculum documents, and relevant scholarly literature related to the 2013 Curriculum. The findings indicate that PAI learning integrates four essential knowledge dimensions. Factual knowledge encompasses students’ understanding of terminology, vocabulary, symbols, and sources of Islamic teachings. Conceptual knowledge involves comprehension of definitions, classifications, general principles, and structural relationships within religious concepts. Procedural knowledge is reflected in students’ mastery of religious practices, such as the steps of ablution and the implementation of Hajj rituals. Meanwhile, metacognitive knowledge emphasizes students’ awareness of their own learning processes, including memorization and reflection on Qur’anic verses and Hadith. The study implies that integrating these knowledge dimensions through a holistic instructional approach can enhance the effectiveness of PAI learning and support students’ higher-order cognitive development, enabling them to understand and apply Islamic teachings more meaningfully